Awareness and access to mass media sources of information about modern family planning methods among women with disabilities in Nigeria: An analysis of 2018 demographic and health survey - Zandam, Hussaini; Mitra, Monika; Mitra, Sophie (Frontiers in Global Women's Health, 2022)
Background: Family planning is the foundation of sexual and reproductive health, and necessary for achieving the Sustainable Development Goals. Yet, the needs of women with disabilities and their access to these services have been neglected for decades, especially in Low and Middle-income Countries. To improve utilization of these services among women with disabilities, they have to be aware and informed about the services. This study was conducted to examine awareness and mass media sources of information on family planning between women with and without disabilities. Methods: This study used data from the 2018 Nigeria Demographic and Health Surveys (NDHS). Our analytic sample included 26,585 women between 15-49 years of age who answered the disability module. We compared demographics and socioeconomic characteristics of women with and without disabilities using the chi-square test for categorical variables. In addition, we conducted logistic regressions to estimate the unadjusted and adjusted odds ratio (with 95% confidence intervals) for level of awareness and mass media sources of information on modern contraceptive methods, using women without a disability as the reference group. Results: Finding showed that women with disabilities have poor awareness about family planning compared to women without disabilities even after adjusting for all covariates (AOR=0.42, 95% CI: 0.23-0.76 p<0.05). We also found that women with disabilities are less likely to receive information about family planning from any of the available mass media channels even after adjusting for covariates (AOR = 0.46, 95% CI: 0.22–0.98, p<0.05). Conclusions: The study revealed that women with disabilities Nigeria have poor awareness about modern family planning methods compared to non-disabled women. They are also less likely to receive information about modern family planning methods compared to non-disabled women. To effectively reach women with disabilities, information barriers must be eliminated, coupled with increased opportunities to access family planning information. Donors, government, and other relevant stakeholders should consider funding inclusive campaigns and explore other mechanisms for disseminating family planning information to women with disabilities.